The Effect of Import-Export on Economic Growth in Batam City, Indonesia - Salsabila Zahwa Adinda; Yusrizal Yusrizal; Muhammad Ikhsan Harahap (International Journal of Economics Development Research (IJEDR), 2023)
The purpose of this research is to generally determine the influence of economic growth with export and import figures in Batam City. Batam City has a policy that provides additional value in international trade that is Free Trade Zone or tax-free zone. Export and import activities are called interstate trade, the purpose is to see the influence of exports and imports on the economic growth of Batam City. The research method is quantitative with multiple linear regression supplemented by secondary data from the Central Statistics Agency (BPS) from 2013 to 2022 where the independent variable is export-import and the dependent variable is the economic growth of Batam City. The results of the study are that the export-import variable has a positive and significant effect on the economic growth of Batam City. Based on the determination results, it shows that 74% of the export and import variables contribute significantly to the economic growth of Batam City.